2018
DOI: 10.1002/pad.1819
|View full text |Cite
|
Sign up to set email alerts
|

The enabling role of institutional entrepreneurs in the adoption of IPSAS within a transitional economy: The case of Estonia

Abstract: Summary In the light of neoinstitutional theory and by adopting case study research methodology, this article explains the adoption of International Public Sector Accounting Standards for modernizing public sector accounting in Estonia. This article reveals that the smooth—yet gradual—adoption of International Public Sector Accounting Standards‐compliant accounting systems was enabled by the involvement of powerful actors (i.e., institutional entrepreneurs) with foreign and/or business backgrounds. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 51 publications
1
38
0
1
Order By: Relevance
“…First, we have delineated that public sector accounting reforms across emerging economies have not been uniform, presenting practice diversity across countries, ranging from the adoption of the Cash Basis IPSAS to accrual accounting to other fragmented approaches. This practice diversity challenges the global debate of public sector accounting harmonisation articulated by international organisations and standard setters (Argento et al, 2018). Next, extending the findings of prior work in emerging economies (Busca et al, 2016;Goddard et al, 2016;Adhikari et al, 2013 andRajib et al, 2019), we have illustrated why the diffusion of public sector accounting reforms and their adoption by emerging economies, as championed by international organisations, has remained ineffective in practice.…”
Section: Discussionsupporting
confidence: 57%
“…First, we have delineated that public sector accounting reforms across emerging economies have not been uniform, presenting practice diversity across countries, ranging from the adoption of the Cash Basis IPSAS to accrual accounting to other fragmented approaches. This practice diversity challenges the global debate of public sector accounting harmonisation articulated by international organisations and standard setters (Argento et al, 2018). Next, extending the findings of prior work in emerging economies (Busca et al, 2016;Goddard et al, 2016;Adhikari et al, 2013 andRajib et al, 2019), we have illustrated why the diffusion of public sector accounting reforms and their adoption by emerging economies, as championed by international organisations, has remained ineffective in practice.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, this seems to be particularly relevant in standardization, as Brunsson et al (2012, p. 622) found that "instead of changing its practices, an organization represents them so that they appear to be in line with a particular standard". We therefore call for more in-depth case studies on the translation of accounting standards (such as those by Adhikari et al, 2019;Argento et al, 2018;Goddard et al, 2016). Third, differences do not only exist between countries but also within countries, when it comes to regional and local governments.…”
Section: Discussionmentioning
confidence: 99%
“…The Continental Rechtsstaat governments issued specific budgeting and reporting laws covering the accounting standards (Austria and Switzerland;Bauer et al, 2011). Other countries either established common national accounting standards valid for both the public and the private sector (Estonia and Poland; Argento et al, 2018) or issued specific standards for public sector organizations (PSOs; France and Sweden). As already mentioned, the UK has implemented IFRS instead of IPSAS.…”
Section: Extent Of Ipsas Implementation and National Deviationsmentioning
confidence: 99%
“…A certain degree of receptivity to change (Lapsley and Pettigrew 1994) is necessary for governments to successfully modify their budgeting systems. Such receptivity is influenced by the tension between exogenous forces and endogenous forces active within a specific country (see also Greenwood and Hinings 1996;Ter Bogt and Van Helden 2000;Argento, Peda, and Grossi 2018).…”
Section: Endogenous Pressures For Pbb Convergence and Divergencementioning
confidence: 99%